Effects of Lactobacillus plantarum on Physicochemical Properties and Volatile Flavor Substances of Blueberry Juice during Fermentation and Storage - Maowen LIAO; Chen HAN; Wei LIU; Yanlin LI; Changlin CHEN; Huaiyu YUAN; Yan ZHOU; Ke LI; Huajia LI (Shipin gongye ke-ji, 2025)
In order to understand the effects of Lactobacillus plantarum on physicochemical properties and volatile flavor substances of blueberry juice during fermentation and storage stages. Fresh Baldwin was used as raw material and Lactobacillus plantarum b-1 was used as starter culture, the changes of physicochemical properties and viable bacterial counts during the fermentation and storage were detected. Moreover, HPLC and headspace solid-phase microextraction gas chromatography (HS-SPME-GC/MS) were used to measure the changes of organic acids and flavor metabolites, finally the quality of flavor was analyzed during fermentation and storage. The results showed that the viable bacterial count of blueberry juice reached 108 CFU/mL after 24 h fermentation, and the viable bacterial count was 6.4×107 CFU/mL after 28 d of storage. Furthermore, the physicochemical properties of the blueberry juice had a great change during the fermentation, for example, the content of the total acid gradually increased during the fermentation process, while the pH value showed a significant decreasing trend (P<0.05). In addition, a total of six organic acids were detected during fermentation and storage, of which lactic acid was a product after fermentation. The distribution of volatile flavor substances at the end of fermentation were alcohols>ketones>esters>aldehydes>alkanes>alkenes. Furthermore, the results based on PCoA and OPLS-DA showed that the flavor metabolites of fermented blueberry juice were significantly different during the fermentation and storage periods, with 14 and 9 different metabolites were detected, respectively. Moreover, the relative contents of linalool and geraniol were increased in fermented blueberry juice which could enhance citrus, floral and rose aromas. In conclusion, this study provides scientific support for the application of Lactobacillus plantarum on the fermentation of blueberry juice.